2010
DOI: 10.1063/1.3356980
|View full text |Cite
|
Sign up to set email alerts
|

High resolution magnetostriction measurements in pulsed magnetic fields using fiber Bragg gratings

Abstract: We report on a new high resolution apparatus for measuring magnetostriction suitable for use at cryogenic temperatures in pulsed high magnetic fields which we have developed at the Hochfeld-Magnetlabor Dresden. Optical fibre strain gauges based on Fibre Bragg Gratings are used to measure the strain in small (∼ 1 mm) samples. We describe the implementation of a fast measurement system capable of resolving strains in the order of 10 −7 with a full bandwidth of 47 kHz, and demonstrate its use on single crystal sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 9 publications
1
71
0
Order By: Relevance
“…were measured using a fiber Bragg grating (FBG) technique [32,33] consisting of recording spectral information of the light reflected by a 0.5-mm-long Bragg grating inscribed in the core of a 125 µm telecom optical fiber. The FBG section of the fiber is attached to the sample to be studied, and changes in the grating spacing are driven by changes in the sample dimensions when the temperature or magnetic field is changed.…”
Section: Methodsmentioning
confidence: 99%
“…were measured using a fiber Bragg grating (FBG) technique [32,33] consisting of recording spectral information of the light reflected by a 0.5-mm-long Bragg grating inscribed in the core of a 125 µm telecom optical fiber. The FBG section of the fiber is attached to the sample to be studied, and changes in the grating spacing are driven by changes in the sample dimensions when the temperature or magnetic field is changed.…”
Section: Methodsmentioning
confidence: 99%
“…• between the b and c axes at T = 4 K. 10 Previous work on GdSi [12][13][14] has shown that the antiferromagnetic order is robust up to approximately 20 Tesla at cryogenic temperatures. However, the H-T phase diagram is not complete, [12][13][14][15] and a detailed understanding of the spin structure is missing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the H-T phase diagram is not complete, [12][13][14][15] and a detailed understanding of the spin structure is missing. Through a combination of the resistivity ρ(T , H ), magnetization M(T , H ), and synchrotron x-ray diffraction, we map out the full phase diagram and spin structures for magnetic fields applied along all three crystal (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Daou et al (12) recently developed a very sensitive, all-optical technique based on fiber Bragg gratings to measure magnetostriction (MS) in ultrahigh pulsed magnetic fields, thereby enabling strain measurements of materials that require high magnetic fields to overcome strong antiferromagnetic spin interactions. Here we combine five essential advances, used to reveal new magnetic textures in SrCu 2 ðBO 3 Þ 2 .…”
mentioning
confidence: 99%